Experimental progress in freestanding oxide membranes designed by epitaxy - Varun Harbola; Ruijuan Xu; Seung Sae Hong (Advances in Physics: X, 2025)
Transition metal oxides are renowned for a plethora of functional properties of both scientific and technological implications. Recent advances in freestanding oxide membranes have introduced many opportunities for oxide materials inaccessible by bulk crystals and thin films. The advent of new low-dimensional oxide materials, leveraging both precise epitaxial design and the flexibility of freestanding geometries, offers a unique platform for tuning strain, engineering heterointerfaces, and enabling novel device architectures. In this article, we highlight key experimental progress in the field, spanning from innovative materials synthesis to emerging device applications.